5-(3, 4, 5-trimethoxybenzoyl)-4-methyl-2-(p-tolyl) imidazol (BZML) targets tubulin and DNA to induce anticancer activity and overcome multidrug resistance in colorectal cancer cells. (5th January 2020) - Bai, Zhaoshi; Liu, Xiaolin; Guan, Qi; Ding, Nianyang; Wei, Qing; Tong, Bending; Zhao, Min; Zhang, Weige; Ma, Lingman
Abstract: Colorectal cancer (CRC) is one of the most common malignancies, and multidrug resistance (MDR) reduces the efficiency of anticancer drugs. Therefore, the development of novel anticancer drugs that are highly active against CRC with MDR is urgently needed. Our previous study showed that 5-(3, 4, 5-trimethoxybenzoyl)-4-methyl-2-(p-tolyl) imidazol (BZML) is not a P-glycoprotein (P-gp) substrate and has a potent anticancer effect against paclitaxel -sensitive or -resistant non-small-cell lung cancer (NSCLC) in vitro and in vivo . In the present study, we found that BZML exhibited strong anticancer activity not only in sensitive CRC cells (SW480 and HCT-116 cells) but also in intrinsically drug-resistant CRC cells (Caco2 cells). In addition, by targeting the colchicine binding site, BZML inhibited tubulin polymerization, which induced G2/M phase arrest, and it caused DNA damage by directly targeting DNA or producing ROS. Further, BZML induced apoptosis through the time-dependent ROS-mediated mitochondrial apoptotic pathway in the CRC cells. Additionally, BZML inhibited P-gp-mediated drug efflux and enhanced the inhibition of the cell growth that had been induced by paclitaxel or doxorubicin in Caco2 cells. In summary, BZML is a multi-targeted anticancer drug that targets tubulin and DNA, and the mechanisms underlying its potent anticancer activity involve disrupting microtubule assembly, causing DNA damage, inducing cell cycle arrest and eventually activating the ROS-mediated mitochondrial apoptotic pathway in SW480, HCT-116 and Caco2 cells. Therefore, the novel compound BZML is a promising anticancer drug that has tremendous potential for CRC treatment, especially for the treatment of drug-resistant CRC.